PENGARUH ADDICTION GAME ONLINE TERHADAP KONSENTRASI BELAJAR SISWA SMAS TAMAN MULIA KABUPATEN KUBU RAYA - Novika, Katarina; Aminuyati, Aminuyati; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this study was to study the effect of online game addiction on the concentration of class XI MIA / IIS SMAS Taman Mulia in Kubu Raya District. The research method used in this research is quantitative descriptive, where the participation taken is students who like online games. To determine the population of researchers using accidental sampling techniques and questionnaires, observation and documentation. Online games provide the "online community" feature so that online games are made as social activities, so they will have an impact on student learning concentration. gamers will have an addiction to play which will cause concentration of learning which has a negative impact. From the results of the analysis conducted with Fcount <Ftable or 0.997 <4.08, the proposed hypothesis is not agreed about there is nothing between online game addiction (X) to the concentration of student learning (Y).Â Keywords: Addiction Online Game, Learning Concentration, Students